Yoga Asanas Sebagai Penunjang Konsentrasi Belajar Siswa - Ni Putu Erlina Partini (Jurnal Yoga dan Kesehatan, 2018)
The concentration of learning plays an important role in the learning process. However, with the development of Science and Technology at this time, the concentration of student learning is not necessarily ownedby students. Concentration of mind is a state of learning that requires calm, comfort, someone’s attentionin understanding the content of the lesson faced. When a student is not able to focus on the lesson beingobtained, students will not be able to concentrate, so students will experience forgetfulness in the subjectsbeing obtained. One training that is considered capable of training mind concentration is yoga. Yoga ispart of Hindu philosophy, besides the teachings of yoga listed in the Patanjali Yogasutra are also found inIndian philosophy, Sad Darsana. Both in the teachings of Patanjali and Sad Darsana, both of them fully explain the eight stages of self-control called Astanggayoga. Astanggayoga consists of, yama, nyama, asanas,pranayama, pratyahara, darana, dyana and samadhi in Sarasvatī (2002)